The Establishment of a Rock Creep Model by Using Creep Bodies via an Improved Gene Expression Programming Algorithm - Pingyang Fan; Junhua Chen; Chuankun Qiu; Junwen Chen; Shan Gao; Jiqing Hou; Min Wang (Applied Sciences)
Rock creep commonly appears in rock mass engineering, and it should be paid appropriate attention. In this paper, studies on creep constitutive models of rocks were reviewed, and it was found that the types of creep constitutive models can generally be classified into two categories: theoretical formulas and combinations of creep bodies. Moreover, the combination of creep bodies has been used mainly for describing the creep characteristics of rocks; however, creep constitutive models have been constructed based on the subjectivity of studies in most cases, which is not objective or scientific enough. To avoid the subjectivity of establishing the creep constitutive model by using creep bodies, improved gene expression programming was utilized to construct the creep model. To verify the validity of the proposed method, two examples were given, and the corresponding creep constitutive models were obtained. The calculation results indicated that the proposed improved gene expression programming can be applied to establish a creep constitutive model in practice.